Presentation of the hypothenar hammer syndrome as a low incidence aneurysmal disorder of the ulnar artery. (August 2021) - Moradi, Arash; Hajian, Abbas
Abstract: Introduction and importance: The hypothenar hammer syndrome (HHS) is either rare or underdiagnosed condition that arises from vascular insufficiency of the ulnar artery in the hand. The most common accused mechanism is repetitive blunt trauma to hypothenar region while activating the latter as a hammer to do the job. Case presentation: A 48 year old woman worked as a master of university claimed from pain and numbness in her left hand concurrent with a pulsatile mass. The second case was a 48 year old man who was a mechanic engineer in automotive industry that claimed of a pain and pulsatile mass in his non-dominant left hand. Clinical discussion: Ulnar artery enters the hand from Guyon's canal where fixes to adjacent structure and is susceptible for injury. Aneurysmal formation is an outcome of arterial trauma which could result in distal necrosis if remains untreated. Conclusion: This study has revealed that even whether a single blunt trauma or writing with pen could lead to aneurysmal formation. It has also showed primary aneurysmal resection with no further surgical procedure is both safe and reliable if digital ischemia is not concurrently present. Highlights: Hypothenar hammer syndrome could make irreversible digital ischemia if remains undiagnosed. Local minor trauma to hypothenar region like writing with pen could lead to aneurysmal formation. Primary surgical resection of aneurysm without further vascular graft is safe to save distal function.